Clinical Significance of Breath Hydrogen as an External Variable of the Redox Environment - Teruo Kiyama (Hydrogen, 2026)
Hydrogen (H2) is a common product of carbohydrate fermentation by the intestinal microbiota, transferred to the blood along the pressure gradient, and exhaled. As H2 is not produced or metabolized in human cells, alveolar H2 is distributed throughout the human body, including cellular organelles such as mitochondria, owing to systemic circulation and gas exchange. The electron transport chain comprises a series of oxidation–reduction (redox) enzymes in the mitochondria of human cells that facilitate adenosine triphosphate (ATP) synthesis. The catalytic activity of electron-transport enzymes is optimized at certain electrochemical potentials, as is hydrogen ion activity (pH). However, the human body is an aqueous system that must be electrically neutral. Membrane potentials exist between the interior and exterior of human cells because of the unequal distribution of ions across the membrane. The single-electrode potential can only be assessed relative to that of another electrode (i.e., a reference electrode). The electrochemical potentials relative to a standard hydrogen electrode (SHE) were measured; it was found that H2 partial pressure was a fundamental factor that affected the SHE, pH, and the reversible hydrogen electrode. The H2 partial pressure is not a unit used to characterize the human body; therefore, breath H2 is an external variable in the redox environment in the human body.